Preliminary investigation on the correlations among self-perceived health, dietary behavior, and sarcopenia measurements in Taiwanese adults - Lai, Kuan-Ching; Tsui, Tsen-Hsuan (Progress in Nutrition, 2021)
Due to population aging in [removed for blind review] and in countries worldwide, promotion of active aging, reduction of sarcopenia incidence, balanced diet and sufficient protein intake, and reduction of refined sugar intake have become particularly critical among older adults. This study investigated the correlations between the perceived health, dietary behavior and sarcopenia measurements of [removed for blind review] adults. This study conducted a questionnaire survey to collect data on participants’ diets for the preceding three days; on habit and frequency of exercise; and on total daily intake of protein, refined sugar, and calories. The questionnaire contained 43 items, with an average content validity ratio of 0.9. The participants were also evaluated using a sarcopenia index comprising four measurement items: body mass index, body fat percentage, grip strength, walking speed for a distance of 6 meters, and muscle mass. The results showed the higher the total daily calorie intake, the higher the daily intake of refined sugars. A low total daily intake of protein is associated with low muscle mass. The older age, lower total self-perceived health score and lower the grip performance were correlated. Older adults should be encouraged to engage in outdoor activities, a health-promoting lifestyle, social activities, and regular exercise for enhancing their positive psychological sate, preventing sarcopenia, and facilitating active aging and quality of life.